Effects of interactive loading interfaces for virtual reality game environments on time perception, cognitive load, and emotions - Huang, Yi-Ting; Hsu, Chih-Chieh; Wang, Tzu-Hsuan (Frontiers in Virtual Reality, 2025)
As virtual reality (VR) games are data-heavy, not only do they take time to load, but wearing a VR headset while waiting can also cause anxiety and agitation in players. This study thus focused on the design of VR loading interfaces, which is an underexplored area in VR research. We investigated how different levels of interaction and visual stimulation affect users’ psychological and behavioral responses. Drawing on theories of time perception and the stimulus-organism-response (SOR) model, we designed loading interfaces for a VR headset integrated with a physiological data collection module. Questionnaire surveys were also used to collect data from 58 participants on their emotions, time perceptions, and cognitive load experience with interactive and non-interactive VR loading interfaces. The results showed that interactive interfaces shortened users’ perception of waiting times, and increased positive emotions and decreased negative emotions while users waited for the game to load. Additionally, users of interactive interfaces were less negatively affected by visual stimulation, whereas in non-interactive interfaces, visual stimulation improved time perception and emotional response. These findings expand the application of SOR theory to VR waiting experiences and highlight the importance of interactivity and visual elements in optimizing the waiting experience, thus contributing to a better understanding of user needs in VR environments.